Application of Deep Learning Techniques in the Development of Predictive Maintenance and Fault Detection in Electric Motors - , Stanley Washington Ferreira de Rezende; , Paulo Elias Carneiro Pereira; , Bruno Pereira Barella; , Alexsander Lindolfo Lima; , Roberto Mendes Finzi Neto; , Jose dos Reis Vieira de Moura Jr. (Archives of Current Research International, 2023)
During the last two decades, there has been remarkable growth in the processing capacity of computers and the evolution of digital cameras. As a result, the thermographic technique and thermal analysis became more applied in electromechanical maintenance due to the low measuring device cost. Simultaneously, new methods based on Deep Learning focused on image and video processing have emerged. In this sense, this contribution aims to verify the applicability of using the deep learning technique of convolutional neural networks to classify patterns of thermographic images of a bench grinder. The methodology used was the collection of thermographic pictures of a bench grinder after starting, without, and after applying loads to the discs. This procedure induced a temperature increase in the grinding machine housing since some types of faults in electric motors can be diagnosed due to over-temperature by thermographic inspection. Furthermore, a Python computational code was developed using a convolutional neural network to classify different grinder operation profiles based on thermal images. In conclusion, the technique proved promising for diagnosing motor failures by thermography and can be implemented in automatic predictive maintenance routines.